Synthesis and Structural Study on Co Substituted ZnO Nanoscale Crystals - Mote, V.D.; Huse, V.R.; Purushotham, Y.; Dole, B.N. (Asian Journal of Chemistry, 2011)
Cobalt substituted ZnO nanopowders with compositional formula Zn1-xCoxO (x = 0.00, 0.05 and 0.10) were prepared by co-precipitation method at low temperature. The crystal structure, lattice parameters and average grain size of pure and Co substituted ZnO nanopowders were determined by X-ray diffraction technique. The XRD results indicate that the samples have hexagonal (wurtzite) crystal structure and there is no secondary phases observed. The lattice parameters ‘a’ and ‘c’ decrease with increasing Co content, it may be due the larger ionic radii of Zn2+ as compared to the Co2+. The X-ray density reduces with increasing Co concentration, indicating the homogeneous substitution of Co2+ for Zn2+ in wurtzite ZnO structure. The average grain size was estimated from width of XRD using Scherrer's equation, it is observed that the grain size decreases with increasing Co content. The parameter ‘u’ (z coordinate of the oxygen atoms) of the wurtzite structure of Zn1-xCoxO increases linearly with increasing Co concentration. The parameter ‘u’ increases as strain increases with Co concentration owing to the lattice distortion.